2014
DOI: 10.1111/1469-0691.12466
|View full text |Cite
|
Sign up to set email alerts
|

Why is mucormycosis more difficult to cure than more common mycoses?

Abstract: Although considered to be a rare infection, mucormycosis (zygomycosis) has emerged as the second most common invasive mould infection. Despite the advent of newer antifungal agents, mortality rate of mucormycosis remains exceedingly high. Successful management of mucormycosis requires early diagnosis, reversal of underlying predisposing risk factors, surgical debridement and prompt administration of active antifungal agents. However, mucormycosis is not always amenable to cure. There are challenging obstacles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
140
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(151 citation statements)
references
References 68 publications
1
140
1
9
Order By: Relevance
“…The epidemiology of zygomycosis is still unclear because of the difficult diagnosis [161]. The mortality of zygomycosis is high and has been estimated at 50-100%, giving a higher mortality index than either systemic candidiasis or aspergillosis [160,[162][163][164].…”
Section: Cryptococcosismentioning
confidence: 99%
“…The epidemiology of zygomycosis is still unclear because of the difficult diagnosis [161]. The mortality of zygomycosis is high and has been estimated at 50-100%, giving a higher mortality index than either systemic candidiasis or aspergillosis [160,[162][163][164].…”
Section: Cryptococcosismentioning
confidence: 99%
“…For comparison: the sinonasal -7.1% and sinonasaloorbital -6.1% forms were not often found. This disease may occur in all patients regardless of age and gender [9,12]. Often the most vulnerable age group were young adults with varying degrees of deficiency of the immune system and also those treated for other systemic diseases.…”
Section: Incidence and Prevalencementioning
confidence: 99%
“…Diabetes mellitus, malignancies, severe injuries and transplantations were most frequently mentioned as predisposing factors in world literature. Uncontrolled diabetes and trauma dominate in developing countries, while in highly developed countries, diabetes and cancer seem to be most often related to any forms of fungal infection [12]. Roden's et al [13] research showed that the most frequently predisposing factor is diabetes, present in 36% cases, while others are 17% forms of various malignancies, while 95% of them are hematological tumors.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Challenging host immune response is another possible reason that may play a role. 13 There are challenging obstacles that lead to difficulties in the management of invasive mucormycosis by amphotericin B. These include unique host-based risk factors for mucormycosis, the fungus' resistance to innate host defenses and distinctive features of its immunopathogenesis, such as extensive angioinvasion, increased virulence and use of chelators by the fungus as siderophores.…”
mentioning
confidence: 99%